The Law of Literature - Brlek, Tomislav (Array, 2003)
In the context of the doxographic discourses proliferating in the institutionally most prominent areas of literary studies, it would seem relevant to pose the question whether literature can be put under the jurisdiction of various politico-socio-historical interpretative methodologies – that privilege ideological readings focusing mostly and often exclusively on the semantic level of the text – and still remain “ an institution constantly putting its own institutionalty into question, ” as Derrida defines it.